Legal Regulation of Agricultural Cooperation: New Approaches and Prospects for Developing Rural Areas - BAKYTZHAN, Kalymbek; YERKINBAYEVA, Lazzat; NURMUKHANKYZY, Daniya; ZHUSUPBEKOVA, Madina; NESIPBAYEVA, Indira (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020DO - 10.14505//jemt.11.7(47).19, 2020)
Throughout the post-independence period, the development of agriculture and rural areas has been among the main priorities of Kazakhstan's economic policy. This study considers new approaches and prospects for the legal regulation of agricultural cooperation and the development of rural areas. The article analyzes the legal regulation of agricultural cooperation in the Republic of Kazakhstan and foreign countries. The authors have identified the main constraining factors to the development of agricultural cooperative societies, in particular, and rural areas, in general. They have also determined the key measures for developing agricultural cooperation and rural areas, as well as provided a detailed overview of such measures. The study results prove that the formation of a multi-level system of agricultural cooperative societies, functioning in collaboration with state (local) authorities, contributes to the development of rural areas.